2011
DOI: 10.1038/ng.1047
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study in Han Chinese identifies multiple susceptibility loci for IgA nephropathy

Abstract: We performed a two-stage genome-wide association study of IgA nephropathy (IgAN) in Han Chinese, with 1,434 affected individuals (cases) and 4,270 controls in the discovery phase and follow-up of the top 61 SNPs in an additional 2,703 cases and 3,464 controls. We identified associations at 17p13 (rs3803800, P = 9.40 × 10(-11), OR = 1.21; rs4227, P = 4.31 × 10(-10), OR = 1.23) and 8p23 (rs2738048, P = 3.18 × 10(-14), OR = 0.79) that implicated the genes encoding tumor necrosis factor (TNFSF13) and α-defensin (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
276
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 266 publications
(295 citation statements)
references
References 46 publications
17
276
1
1
Order By: Relevance
“…We manually curated a list of SNPs that both passed genome-wide significance and were associated with kidney disease traits (Table S7). [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] To acquire independent loci, we removed any SNPs having r 2 R 0.2. In total, we analyzed 110 leading SNPs and 2,357 tagging SNPs with r 2 R 0.8 (Table S7).…”
Section: Kidney Eqtl Highlights the Genetics Of Disease Traitsmentioning
confidence: 99%
“…We manually curated a list of SNPs that both passed genome-wide significance and were associated with kidney disease traits (Table S7). [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] To acquire independent loci, we removed any SNPs having r 2 R 0.2. In total, we analyzed 110 leading SNPs and 2,357 tagging SNPs with r 2 R 0.8 (Table S7).…”
Section: Kidney Eqtl Highlights the Genetics Of Disease Traitsmentioning
confidence: 99%
“…Many LGWS and GWAS in both familial and sporadic IgAN suggest that there is a strong genetic component in the disease. [7][8][9][10][11][12] However, most studies have not evaluated the contribution to this complex disorder of other forms of genetic variation, such as structural variations, mainly in the form of CNVs. 15 Indeed, CNVs have recently been shown to have an important role in complex disease phenotypes as psoriasis, 30 rheumatoid arthritis 31 and systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…)del, containing the COL11A2 (collagen, type XI, alpha 2 isoform 1), were found in very close proximity to SNPs that gave multiple associations in the MHC class I region and HLA complex group genes identified by three independent GWAS. [10][11][12] Moreover, the loss chr6.hg18:g.(?_134 801-335)_(134 848 458_? )del overlapped with the region named IGAN1 identified in a GWLS.…”
Section: Identification Of Concordant Aberrations In Igan Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Association studies identified distinct loci on chromosomes 6p21, 8p23, 17p13, 22q12, 1q32. 6,7 On the other hand, classical linkage studies performed on AD families identified additional loci on chromosomes 2q36, 4q26-31, 6q22, 17q12-22, [8][9][10] lending further support to the complex etiology and broad genetic heterogeneity of the disease.…”
Section: Introductionmentioning
confidence: 88%